An Ethnographic Study of Palliative and End-of-Life Care in a Nigerian Hospital: Impact of Education on Care Provision and Utilization. (September 2020) - Agom, David A.; Onyeka, Tonia C.; Ominyi, Jude; Sixsmith, Judith; Neill, Sarah; Allen, Stuart; Poole, Helen
Most clinicians receive little or no palliative care (PC) education. Similarly, patients and their families receive little or no information on PC. Our study explored education in PC, while examining for its impacts on service delivery and utilization from the perspective of health care professionals (HCPs), patients, and their families. An ethnographic approach was utilized to gather data from 41 participants. Spradley's ethnographic analytical framework guided data analysis. Two themes identified were inadequate HCPs' knowledge base and impact of service-users' inadequate health education. The findings show that most HCPs had no formal education in PC, attributed to the lack of PC residency programs and the absence of educational institutions that provide such education. Patients and families also conveyed poor understandings of their illness and palliation, rooted in the HCP culture of partial disclosure of information about their diagnosis, care, and prognosis. Findings suggest a cultural shift that supports PC education for professionals is required to promote realist medical approach in the care for patients with life-limiting illnesses.